Identificar modelos matemáticos y métricas que extraídas desde el código fuente permitan el cálculo y análisis de Green Software - Chavez Saraguro, Edison Enrique (2018)
Abstract:The present titration work exposes a study focused on the analysis of source code and is carried out as a consequence of the growing interest in developing applications that support the development of sustainable software. One of the techniques used is the static analysis, which is based on the analysis of the source code, extraction and identification of code features and metrics, allowing to ensure the quality of writing and design of software applications with green characteristics in mind. Regarding the quality of software applications. As a result of this research work is designed, implemented and validated a web prototype that allows static analysis based on features and green metrics (developed solution). The process that uses the prototype begins with the load of the source code and extraction of characteristics that allow to calculate the metrics and results of analysis of applications built with JAVA programming language. The metrics and results will be calculated using the mathematical models or formulas proposed to determine the quality of the application that the user has developed.